2014
DOI: 10.1088/1751-8113/47/4/045201
|View full text |Cite
|
Sign up to set email alerts
|

Group classification of variable coefficient generalized Kawahara equations

Abstract: An exhaustive group classification of variable coefficient generalized Kawahara equations is carried out. As a result, we derive new variable coefficient nonlinear models admitting Lie symmetry extensions. All inequivalent Lie reductions of these equations to ordinary differential equations are performed. We also present some examples on the construction of exact and numerical solutions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…and the authors of [15] did the same earlier for the special case when f (u) = u n . While equation (3) is slightly more general than (2), the generalized symmetries of either (2) or (3) to the best of our knowledge were not studied in full generality in the earlier literature.…”
Section: Resultsmentioning
confidence: 75%
“…and the authors of [15] did the same earlier for the special case when f (u) = u n . While equation (3) is slightly more general than (2), the generalized symmetries of either (2) or (3) to the best of our knowledge were not studied in full generality in the earlier literature.…”
Section: Resultsmentioning
confidence: 75%
“…The set of admissible transformations of a class of differential equations naturally possesses the groupoid structure with respect to the standard operation of transformations composition [12]. More details and examples on finding and usage of admissible transformations for generalized fKdV equations as well as definitions of different kinds of equivalence groups can be found in [6,15].…”
Section: Admissible Transformationsmentioning
confidence: 99%
“…The presence of variable coefficients in a differential equation that model certain real-world phenomenon often allows one to get better description of the phenomenon but, at the same time, makes the related studies of this equation, including group classification problems, more difficult. In recent works on Lie symmetry analysis it was shown that the usage of admissible transformations in many cases is a cornerstone that leads to exhaustive solution of group classification problems [1,6,12,13]. That's why we firstly investigate admissible transformations in the class (1) in the next section and then proceed with the classification of Lie symmetries in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…Proposition 7 and Section 9. Variable-coefficient generalizations of the Kawahara equation were studied in a similar way in [17,18]. The group classification of Galilei-invariant equations of the form u t + uu x = F (u r ) was carried out in [5,8].…”
Section: Introductionmentioning
confidence: 99%